Our Land, Our People: reconsidering site-specificity in exile. Issue 1 (31st December 2022) - Magnatta, Sarah
ABSTRACT: In 2011, artist Tenzing Rigdol transported over twenty-four tons of soil from Tibet into the exile Tibetan community of Dharamsala, India, for a temporary installation—a site-specific work—titled Our Land, Our People . The exile community walked on, held, and sometimes ingested the soil (a clear marker of the importance of this work to this particular audience), the soil signaling the would-be permanent home of the audience. Despite the increase in global site-specific works over the past decades, few of these projects have navigated the issue of temporality as it relates to audiences in exile communities. By evaluating Rigdol's contribution through the lens of site-specificity as theorized by Miwon Kwon, this essay shows how Our Land, Our People expands the site-specific paradigm as it challenges notions of what makes art site specific; it proposes diasporic communities—communities with implied temporality and often tenuous relationships to their current homes—can serve as the foremost component of the work. I also propose Rigdol's Our Land, Our People breaks with the conventional label "contemporary Tibetan art, " the phrase currently used to describe art created in Tibet and in exile spaces. Our Land, Our People is primarily in dialogue with one audience in particular—the exile community in Dharamsala.